2019
DOI: 10.1055/s-0039-3399540
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Unilateral Cochlear Implantation in Adults: Speech Recognition, Health-Related Quality of Life and Level of Anxiety and Depression: a One- and Three-Year Follow-Up Study

Abstract: Introduction Hearing impairment is a common disease worldwide, with a comprehensive impact, and cochlear implantation (CI) is an intervention for profound hearing impairment. Objective To study the outcome one and three years after unilateral CI on hearing, health-related quality of life and level of depression and anxiety, and the correlation between the outcomes. Second, to study whether age, gender, etiology, operated side, residual hearing or cognitive performance can predict the outcome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…Screening by title and abstract excluded 1263 articles. Full‐text review of the remaining articles excluded 259 publications, resulting in 22 articles being included in the final analysis 29–50 . The search process is summarized in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Screening by title and abstract excluded 1263 articles. Full‐text review of the remaining articles excluded 259 publications, resulting in 22 articles being included in the final analysis 29–50 . The search process is summarized in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…A recent systematic review [ 38 ] mentioned two studies (mean ages: 58.6 and 51.7 years) in which cochlear implantation reduced the symptoms of depression. Bergman et al [ 39 ] found that the level of depression decreased 1 year after implantation in a group of CI users with a median age of 72 years. Conversely, Mertens et al [ 28 ] found no effect of CI use on the levels of anxiety and depression in 24 CI users (mean age: 72 years).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that in most of the studies conducted in this area with patients who underwent cochlear implantation, the older age range was addressed. 11 Many factors that may affect the psychosomatic states of patients in the advanced age group, such as anxiety and depression, may come into play, so patients may be more affected. In addition, due to their advanced age, they can lead a more calm and sedentary life.…”
Section: Discussionmentioning
confidence: 99%